Mindfulness, Experiential Avoidance, and Affective Experience in Older Adults - Pierson, McKenna M. (J Contextual Behav Sci, 2019)
Subjective well-being is comprised of two components: affective experience and life satisfaction. Older adulthood is marked by changes and challenges that have the potential to diminish well-being. As the proportion of older adults in the population rises, it is becoming increasingly important to identify factors that may be protective against these potentially detrimental events. Mindfulness and acceptance constructs have been shown to be associated with affective experience across the lifespan. However, little work has examined which facets of mindfulness drive these associations. The current study aimed to explore the associations between acceptance and mindfulness processes and positive and negative affect in older adults. Eighty-five healthy older adults completed self-report measures of mindfulness, experiential avoidance, and positive and negative affect. Results from linear regression analyses indicated that the act with awareness and nonreactivity facets of mindfulness were particularly important in their contribution to positive affect. Additionally, higher levels of experiential avoidance accounted for significant variance in negative affect. These findings help to elucidate how mindfulness and acceptance processes play a role in affective experience in older adults. Future studies should explore these facets in clinical populations to help create more targeted clinical goals.